Effect of vibrational iterations of magnetized water on the physico-chemical properties of intact water - Novikov, V. V. (Russian physics journal, 2024)
It has already been shown that it is possible to obtain vibrational iterations (artificial material objects) through multiple vibration processing (crossing) of any substance (see Petrova A. et al. (2024)). In this work, using the same crossing technology, vibrational iterations were obtained from water exposed to various magnetic fields. They, like vibrational iterations from high- and low-molecular weight substances, were classified into groups (fractions) according to their physical and chemical properties.